1999
DOI: 10.3354/meps176081
|View full text |Cite
|
Sign up to set email alerts
|

A high frequency time series at Weathership M, Norwegian Sea, during the 1997 spring bloom:the reproductive biology of Calanus finmarchicus

Abstract: The reproductive biology of Calanus finmarchjcus was investigated at a permanent station in the Norwegian Sea (Weathership Stn M, 66" N, 2" E) during a time series between March and June 1997 The temporal development of female abundance, egg production rate and gonad development stage in relation to the phytoplankton production cycle is described Abundance of females, copepodite stage 5 and males as well as female gonad morphology were examlned from MrP2 net samples taken daily from the upper 100 m. Daily egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
106
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 10 publications
12
106
2
Order By: Relevance
“…In 2 of these studies, measured (Irigoien et al 1998) and estimated (Richardson et al 1999) ingestion rates were insufficient to cover the energetic costs of EP. It is possible that in this species of Calanus, internal lipid stores provide most of the energetic requirements and some level of ingested material is required for gonad maturation and subsequent egg production (Ohman & Runge 1994, Niehoff et al 1999. Consistent with this interpretation, the spawning rates predicted in winter of 2000 in the GOM fit with Ivlev relationships relating chl a biomass to EP in this region (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In 2 of these studies, measured (Irigoien et al 1998) and estimated (Richardson et al 1999) ingestion rates were insufficient to cover the energetic costs of EP. It is possible that in this species of Calanus, internal lipid stores provide most of the energetic requirements and some level of ingested material is required for gonad maturation and subsequent egg production (Ohman & Runge 1994, Niehoff et al 1999. Consistent with this interpretation, the spawning rates predicted in winter of 2000 in the GOM fit with Ivlev relationships relating chl a biomass to EP in this region (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…In the Gulf of St. Lawrence, pre-bloom food limitation was demonstrated, as non-egg-producing females captured before the spring bloom and maintained in high food levels in the laboratory produced eggs well before their field counterparts. In contrast, significant rates of EP by C. finmarchicus have been observed at pre-bloom chl a concentrations of only 0.2 to 0.4 µg l -1 (Niehoff et al 1999, Richardson et al 1999, this study). In 2 of these studies, measured (Irigoien et al 1998) and estimated (Richardson et al 1999) ingestion rates were insufficient to cover the energetic costs of EP.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Alternatively, the composition of natural food consumed prior to the experimental incubations of summer-caught copepods may have inhibited egg production. Similarly, Niehoff et al (1999) found that egg production per female during the days following the 1997 spring phytoplankton bloom at Weathership M was substantially less than would have been expected on the basis of laboratory-based relationships with temperature and algal biomass. To summarize both the seasonal effect and the poorly quantified upper temperature limit for egg production, temperature dependency was represented in the nowcast model by a parabolic function which approximated to a Q 10 response fitted to the data of Hirche et al (1998) between 4 and 6 C, but decreased rather than increased at higher temperatures, approaching zero at 13 C (Appendix and Table 6).…”
Section: Egg Production Nowcast Modelmentioning
confidence: 98%
“…Preservation of plankton was with buffered 4% formaldehyde. Samples collected by pump in 1998 by the U.S. GLOBEC Georges Bank program were provided by Edward Durbin of University of Rhode Island, and samples taken in 1997 with vertical nets at Station M in the Norwegian Sea (Niehoff et al 1999) were provided by HansJürgen Hirche and Barbara Niehoff of Alfred-Wegner Institute, Bremerhaven. We sorted eggs of Calanus finmarchicus from both of these sets of formaldehyde-preserved samples.…”
Section: Materials and Proceduresmentioning
confidence: 99%